Macrozoobenthos community structure in restored seagrass, natural seagrass and seagrassless areas around Badi Island, Indonesia. (April 2019) - Asriani, N; Ambo-Rappe, R; Lanuru, M; Williams, S L
Abstract: Seagrass ecosystems play an important role in providing food and protection to the organisms that live in and around seagrass meadows. However, due to heavy pressure from human activities, many seagrass beds have been degraded, with the loss or reduction of important ecological functions. Therefore, seagrass restoration needs to pay attention to the recovery of these ecological functions. This study aimed to determine the success of the seagrass restoration activities around Badi Island, South Sulawesi, Indonesia, in supporting the recovery of ecological functions, as viewed from the macrozoobenthos community structure. Data on macrozoobenthos community structure in transplanted seagrass areas was compared with the macrozoobentos community structure of nearby natural seagrass beds and seagrassless areas. The macrozoobenthos identified comprised 34 species from 3 classes in the seagrass restoration area, 73 species from 9 classes in natural seagrass beds, and 24 species from 4 classes in areas without seagrass. A one way ANOVA test indicated significant differences in macrozoobenthos density between the transplanted areas and natural seagrass beds but not sites without seagrass. Ecological indicators such as the diversity index and evenness index showed a higher level of macrozoobenthos community structure in all the sampling sites. We conclude that, as transplanted seagrasses become established, they can provide ecological functions and serve as habitat for a wider variety of other organisms, as reflected in the community structure of the associated macrozoobenthic organisms.